2018
DOI: 10.1002/cctc.201800246
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Sintering‐Resistant, Single‐Atom Ru Species Dispersed on Zirconia‐Based Catalysts: A DFT and FTIR Study of CO Adsorption

Abstract: Recent studies on the upgrade of cellulosic biomass to renewable chemicals and fuels based on Ru/ZrO2 catalysts have shown that the catalyst contains atomically dispersed, highly stable Ru atoms. FTIR spectra after CO dosage reveal a complex manifold of bands resulting from Ru‐CO carbonyl species. The nature of the atomically dispersed Ru species on monoclinic zirconia, and the origin of their thermal stability are the object of this investigation. Combining density functional theory (DFT) calculations on mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 60 publications
8
50
1
Order By: Relevance
“…The stabilization of Rh atoms on the surface of ZrO 2 via direct bonding with surface OH groups, emerges as a general characteristic and has been observed and reported for other species: Ru on ZrO 2 , [36] Ru on TiO 2 , [34] Pt on TiO 2 , [35,43] and Rh on TiO 2 . [62] The case of Rh on ZrO 2 discussed in this study is just another piece of evidence that there is a general mechanism acting to stabilize single atoms on the surface of titania and zirconia, and that this is related to the presence of hydroxyl groups.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…The stabilization of Rh atoms on the surface of ZrO 2 via direct bonding with surface OH groups, emerges as a general characteristic and has been observed and reported for other species: Ru on ZrO 2 , [36] Ru on TiO 2 , [34] Pt on TiO 2 , [35,43] and Rh on TiO 2 . [62] The case of Rh on ZrO 2 discussed in this study is just another piece of evidence that there is a general mechanism acting to stabilize single atoms on the surface of titania and zirconia, and that this is related to the presence of hydroxyl groups.…”
Section: Discussionsupporting
confidence: 52%
“…As we mentioned above, we recently elucidated the real nature single Ru atoms deposited on ZrO 2 and TiO 2 by using combined DFT and FT-IR methods. [34,36] In particular, we showed that isolated Ru atoms are stabilized as RuO units resulting from the interaction of Ru with a surface hydroxyl group and consequent release of H 2 . This is a general feature, although several variants can be found.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations